Modulation of Serum Brain-Derived Neurotrophic Factor by a Single Dose of Ayahuasca: Observation From a Randomized Controlled Trial - Almeida, Raíssa Nóbrega de; Galvão, Ana Cecília de Menezes; da Silva, Flávia Santos; Silva, Erick Allan dos Santos; Palhano-Fontes, Fernanda; Maia-de-Oliveira, João Paulo; de Araújo, Lobão-Soares Barros; Lobão-Soares, Bruno; Galvão-Coelho, Nicole Leite (Frontiers in Psychology, 2019)
Serotonergic psychedelics are emerging as potential antidepressant therapeutic tools, as suggested in a recent randomized controlled trial with ayahuasca for treatment-resistant depression. Preclinical and clinical studies have suggested that serum brain-derived neurotrophic factor (BDNF) levels increase after treatment with serotoninergic antidepressants, but the exact role of BDNF as a biomarker for diagnostic and treatment of major depression is still poorly understood. Here we investigated serum BDNF levels in healthy controls (N = 45) and patients with treatment-resistant depression (N = 28) before (baseline) and 48 h after (D2) a single dose of ayahuasca or placebo. In our sample, baseline serum BDNF levels did not predict major depression and the clinical characteristics of the patients did not predict their BDNF levels. However, at baseline, serum cortisol was a predictor of serum BDNF levels, where lower levels of serum BDNF were detected in a subgroup of subjects with hypocortisolemia. Moreover, at baseline we found a negative correlation between BDNF and serum cortisol in volunteers with eucortisolemia. After treatment (D2) we observed higher BDNF levels in both patients and controls that ingested ayahuasca (N = 35) when compared to placebo (N = 34). Furthermore, at D2 just patients treated with ayahuasca (N = 14), and not with placebo (N = 14), presented a significant negative correlation between serum BDNF levels and depressive symptoms. This is the first double-blind randomized placebo-controlled clinical trial that explored the modulation of BDNF in response to a psychedelic in patients with depression. The results suggest a potential link between the observed antidepressant effects of ayahuasca and changes in serum BDNF, which contributes to the emerging view of using psychedelics as an antidepressant. This trial is registered at http://clinicaltrials.gov (NCT02914769).